2013
DOI: 10.1080/08927014.2013.776042
|View full text |Cite
|
Sign up to set email alerts
|

Mini-review: Inhibition of biofouling by marine microorganisms

Abstract: Any natural or artificial substratum exposed to seawater is quickly fouled by marine microorganisms and later by macrofouling species. Microfouling organisms on the surface of a substratum form heterogenic biofilms, which are composed of multiple species of heterotrophic bacteria, cyanobacteria, diatoms, protozoa and fungi. Biofilms on artificial structures create serious problems for industries worldwide, with effects including an increase in drag force and metal corrosion as well as a reduction in heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
155
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(160 citation statements)
references
References 143 publications
(154 reference statements)
1
155
0
4
Order By: Relevance
“…This assemblage of microorganisms and EPS is referred to as a biofilm, or slime. The presence of biofilms on surfaces may influence the settlement of propagules of higher organisms such as algal spores (Joint et al 2002, Marshall et al 2006, Mieszkin et al 2013, Patel et al 2003, larvae of barnacles (Dobretsov et al 2013, Hadfield & Paul 2001 and tubeworms (Hadfield 2011, Zardus et al 2008. The colonization by these organisms on surfaces leads to economic and environmental costs, which have been widely reported (Callow & Callow 2011, Fitridge et al 2012, Schultz et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assemblage of microorganisms and EPS is referred to as a biofilm, or slime. The presence of biofilms on surfaces may influence the settlement of propagules of higher organisms such as algal spores (Joint et al 2002, Marshall et al 2006, Mieszkin et al 2013, Patel et al 2003, larvae of barnacles (Dobretsov et al 2013, Hadfield & Paul 2001 and tubeworms (Hadfield 2011, Zardus et al 2008. The colonization by these organisms on surfaces leads to economic and environmental costs, which have been widely reported (Callow & Callow 2011, Fitridge et al 2012, Schultz et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that propagules of marine fouling organisms settle and attach easily on immersed untreated solid surfaces, while many slimy or gel-like surfaces, such as marine algae (Bhadury & Wright 2004) and sea anemones (Atalah et al 2013) are more resistant to epibiosis, has inspired to explore the potential of hydrogels and other highly hydrophilic materials for the control of marine biofouling (Ekblad et al 2008, Larsson et al 2007, Yandi et al 2014, and for informing the development of useful coatings. The prevention of epibiosis of marine organisms is sometimes the combined result of a strongly hydrated surface and, for example, secretion of substances with antifouling activity by the basibiont (Dobretsov et al 2013, Fusetani 2004, Rickert et al 2015, continuous production of mucus (Wahl et al 1998), or other specifically developed antifouling mechanisms. It has also been found that attachment and settlement of marine organisms on synthetic neutral hydrogels or hydrophilic polymers is very low both in laboratory and in marine field tests (up to 1 h exposure to bacteria or algal spores, 48 h incubation with barnacle cyprids, up to two months field immersion) (Ekblad et al 2008, Xie et al 2011, Yandi et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This is a widespread problem in the food industry [1], hospitals [2], and marine [3] and aerospace construction applications [4]. Bacterial biofilms serve as reservoirs for pathogen development, which could lead to infectious diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given the costs of biofouling treatment, power plants require biofouling and biocorrosion control solutions that are economically efficient, easy to apply to the system, as well as environmentally sustainable. This can be achieved by adjusting the timing and magnitude of chlorination in combination with special antifouling surfaces [6,[12][13][14]. There is a need, however, for deeper understanding of the structure of the microbial community responsible for biofouling of the surfaces under real industrial conditions.…”
Section: Introductionmentioning
confidence: 99%